2006
DOI: 10.1111/j.1600-0854.2006.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dynactin Disruption and Dynein Depletion on Axonal Microtubules

Abstract: We investigated potential roles of cytoplasmic dynein in organizing axonal microtubules either by depleting dynein heavy chain from cultured neurons or by experimentally disrupting dynactin. The former was accomplished by siRNA while the latter was accomplished by overexpressing P50-dynamitin. Both methods resulted in a persistent reduction in the frequency of transport of short microtubules. To determine if the long microtubules in the axon also undergo dynein-dependent transport, we ascertained the rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 40 publications
8
74
1
Order By: Relevance
“…Under such a scenario, cytoplasmic dynein could move the MTs either anterogradely or retrogradely depending whether its cargo domain is attached to the actin cytomatrix or to other MTs, though anterograde motion should dominate. Indeed, experiments have confirmed the crucial role of cytoplasmic dynein in MT movement [4].…”
Section: The Transport Network: Microtubule Dynamics In Axonsmentioning
confidence: 89%
See 4 more Smart Citations
“…Under such a scenario, cytoplasmic dynein could move the MTs either anterogradely or retrogradely depending whether its cargo domain is attached to the actin cytomatrix or to other MTs, though anterograde motion should dominate. Indeed, experiments have confirmed the crucial role of cytoplasmic dynein in MT movement [4].…”
Section: The Transport Network: Microtubule Dynamics In Axonsmentioning
confidence: 89%
“…The motility is achieved through molecular motors, which are anchored on actin filaments or longer MTs and exert forces on the transported MT by walking on it. It has in fact been shown that dynein and the actin cortex are responsible for half of the anterograde MT transport in axons while the rest depends on kinesin [269,4]. One thus finds two populations of MTs in the axon: short and mobile MTs which are transported and perform bidirectional motion and long and immobile MTs which serve as structures along which the short MTs can be transported.…”
Section: The Transport Network: Microtubule Dynamics In Axonsmentioning
confidence: 99%
See 3 more Smart Citations